2014
DOI: 10.4028/www.scientific.net/amr.1082.408
|View full text |Cite
|
Sign up to set email alerts
|

An Experimental Study on Anchor Performance of Bare CFRP Tendons with Bond Type Anchor

Abstract: Despite of their outstanding axial strength, CFRP tendons necessitate special anchorage due to their low lateral shear strength. In order to cope with such CFRP tendon, the conventional bond type anchor needs to be improved. The results of bond tests executed on 10-mm diameter CFRP tendons coated with sand and oxide revealed that, even if the average bond strength increases by 3 times compared to the non-coated bare tendon, the coated CFRP tendon still requires excessively long anchored length for bonding. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 1 publication
0
6
0
1
Order By: Relevance
“…Anchor for CFRP Tendon. Jung et al [6] proposed the wedge-, bond-, and swaged-type anchors shown in Table 3 for the CFRP tendon. e swaged-type anchor presents smaller size than the wedge-type or bond-type anchor but needs to pay attention on the swage pressure brought by the change in the inner and outer diameters of the sleeve and the stress concentration occurring at the end of the sleeve in order to improve the anchoring performance (Table 3).…”
Section: Anchor and Prestressing System For Cfrp Tendonmentioning
confidence: 99%
See 1 more Smart Citation
“…Anchor for CFRP Tendon. Jung et al [6] proposed the wedge-, bond-, and swaged-type anchors shown in Table 3 for the CFRP tendon. e swaged-type anchor presents smaller size than the wedge-type or bond-type anchor but needs to pay attention on the swage pressure brought by the change in the inner and outer diameters of the sleeve and the stress concentration occurring at the end of the sleeve in order to improve the anchoring performance (Table 3).…”
Section: Anchor and Prestressing System For Cfrp Tendonmentioning
confidence: 99%
“…Nanni et al [3] evaluated the anchoring performance of 10 different FRP anchors by classifying them into wedge type, potted type, and spike type instead of the 6 types specified by ACI [4] that are clamp type, plug-and-cone type, straight sleeve type, contoured sleeve type, metal overlay type, and wedge type. Other studies related to the anchors for FRP tendon classified them into clamp type, swaged type, spike type, sleeve type, and wedge type [5,6]. e externally bonded reinforcement (EBR) is often cited as the most popular strengthening method using FRP.…”
Section: Introductionmentioning
confidence: 99%
“…또한 충전 재에 모래를 첨가함으로써 에폭시의 부피를 증가시켜 점도를 조절할 수 있고, 열팽창계수를 낮추어 유리전이온도를 조절할 수 있다고 분석하였다 (De Lorenzis et al, 2007) (Han et al, 2007(Han et al, , 2008. 다른 연구로는 부착형 정착 장치를 갖는 긴 장재의 정착에 관한 실험적 연구를 수행하였는데 에폭시, 콘 크리트, 모르타르 등의 5종의 채움재를 이용하여 제작한 실험 체에 대한 부착특성 분석을 수행하고 최적의 충전재에 대해 제시하였다 (Jung et al, 2011). 충전재에 대한 다른 연구로는 다양한 충전재를 매개변수로 하여 긴장용 슬리브 내에서 충 분한 부착강도가 발현될 수 있는 파괴형태를 유도하는 충전 재의 강도를 제시하였다 (Lee et al, 2013).…”
Section: 충전재의 외부 환경에 대한 연구로는 충전재로 모르타르 에폭시에 대하여 동결·융해 실험을 실시하여 모르타르를unclassified
“…Unlike the bonded type, this type of anchor does not require a curing period for the filling material and enables to shorten the length of the sleeve by more than 33%. Jung et al [3] evaluated the anchor performance of the swaging type anchor through an experimental study considering various parameters including the dimensions of the sleeve, and the eventual presence of insert. Their experimental results revealed that the anchor performance of the swaging type anchor varied according to the change in the swaging pressure itself depending on the inner and outer diameters of the sleeve.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, Jung et al [3] examined the variation of stress according to the change in the inner diameter of the sleeve through finite element analysis as shown in Figure 2. This analysis enabled to state the existence of an adequate stress and of corresponding optimal dimensions of the sleeve to secure the tendon anchor performance.…”
Section: Introductionmentioning
confidence: 99%